Legal Reconstruction of Land Ownership Restrictions on Business Use Rights to Plantation Companies Reviewed from the Perspective of Social Justice - Rahim, Abd.; Eddy, Triono; Nadhirah, Ida (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This study discusses the legal reconstruction related to the restriction of land ownership of the Right to Use (HGU) by plantation companies from the perspective of social justice. The concentration of land ownership by large corporations often results in injustice for local communities and small farmers. The study aims to identify key issues in current HGU regulation and propose legal measures that can support a more equitable distribution of land as well as the recognition of the rights of indigenous and local peoples. The research method used is a normative study with a legislative approach and public policy analysis. The data used includes laws and regulations, academic literature, and reports from various related institutions. The results of the study show that it is necessary to limit the maximum area of HGU that can be owned by plantation companies, accelerate the agrarian reform program, and increase transparency and public participation in the process of granting HGU. In addition, stricter supervision and effective law enforcement are also very important to prevent abuse of business use rights. This study concludes that legal reconstruction that prioritizes the principle of social justice can reduce the land ownership gap and improve community welfare. The recommendations submitted are expected to be the basis for policymakers in formulating fairer and more sustainable regulations in the agrarian sector.Keywords: Land; Ulayat; Use; Effort.